First report of Xylella fastidiosa subsp. pauca in Olea europaea in Santa Catarina, Southern Brazil - Canale, Maria Cristina; Cardoza, Yuliet; Chaves Ortiz, Pamella; Mituti, Tatiana; Fernandes, Juliane; Roveri Sabiäo, Rafael; Barbé, Silvia; Brugnara, Eduardo Cesar (Springer, 2025)
The state of Santa Catarina (SC), southern Brazil, is estimated to have nearly 100 hectares dedicated to olive (Olea europaea L.) cultivation, with promising growth prospects. Herein, we report the first detection of Xylella fastidiosa subsp. pauca (Xfp) in olive trees in SC. Xfp was initially identified to cause citrus variegated chlorosis and coffee leaf scorch in Brazil. Since 2013, it has been associated with the Olive Quick Decline Syndrome in Italy, and soon after, in Brazil (Safady et al. 2019). Three trees cv. ‘Koroneiki’ and one cv. ‘Arbequina’, aged 6 years old, exhibited leaf browning and scorch symptoms, along with premature twig and branch dieback (Supplemental Fig. 1), in an experimental orchard in Chapecó. Symptomatic twig samples from those plants and one sample from an asymptomatic ‘Koroneiki’ tree were collected in springer 2023 and summer 2024 and were subjected to DNA extraction using Wizard DNA purification kit (Promega) and PCR amplification of seven housekeeping genes (leuA, petC, malF, cysG, holC, nuoL, gltT) (Yuan et al. 2010). Amplicons were purified and sequenced on both strands. The sequences were edited using the BioEdit 7.0.5.3 software, and consensus sequences were analyzed using the MEGA software. The results of sequencing were compared with available sequences on PubMLST (Jolley et al. 2018). Approximate amplicon size, adjusted without primers, and the allele number identified were: 670 bp for leuA (allele 7), 551 bp for petC (allele 6), 685 bp for malF (allele 7), 608 bp for cysG (allele 9), 399 bp for holC (allele 23), 578 bp for nuoL (allele 17) and 635 bp for gltT (allele 8), which correspond to sequence type (ST) 69 of Xf subspecies pauca [(isolate OliveECB01, PubMLST id:31) (GenBank accession numbers PQ550632-38, respectively to each gene)]. Xfp ST 69 isolates were previously found in Citrus sinensis in Argentina (Coletta-Filho et al. 2017), next to the border with Santa Catarina. This is the first occurrence of this sequence type in Brazil